STAFFING NEEDS ANALYSIS IN THE PHARMACY UNIT OF SANTA MARIA HOSPITAL PEKANBARU 2017 - Monika Noviena Susanto; Vetty Yuliaty Permanasari (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Several previous studies have calculated the workload and the needs of human resources in the pharmacy unit and found that the availability of human resources is still not in accordance with the workload undertaken. This study aims to analyse the workload and human resource requirement in Pharmacy Installation of Santa Maria Hospital Pekanbaru 2017. Methods: This research is descriptive research conducted at Hospital Santa Maria Pekanbaru from January until December 2017. Subject of the research included pharmacist laboratory and pharmaceutical technical personnel (pharmacist assistant). Data collection was done by in-depth interview with key informants and from hospital staffing documents and hospital pharmacy installation documents. Results: Total requirement of pharmaceutical work force during effective day is 40 persons, while requirement during holiday accounted for 21 persons and make it totally 61 persons. Conclusions: With The current number of employee of 54 people, the hospital required an additional seven person to cope with the workload at the Pharmacy unit of Santa Maria Hospital.